PENGARUH KEPUASAN KERJA TERHADAP TURNOVER PEGAWAI PADA PT HADJI KALLA TOYOTA CABANG COKROAMINOTO KOTA MAKASSAR - Salmawati, Sitti; Widhi Kurniawan, Agung; Wardhana Haeruddin, Muhammad Ilham (Indonesian Journal of Research in Economy, 2022)
The purpose of this study was to determine the effect of job satisfaction on turnover intention of employee who work in PT Hadji Kalla Cokrominoto. The subjects in this study were 45 employees working at PT Hadji Kalla Cokrominoto Branch. This research is included in quantitative research where data collection is carried out using a questionnaire. The analytical method used is descriptive quantitative analysis to determine the results of respondents' responses to the variables of performance satisfaction and turnover intention and quantitative analysis to test research hypotheses using SPPS software. The results showed that the job satisfaction variable had a negative and significant effect on turnover intention. This is evidenced by the t-count value of - 8.619 where 8.619 > t table (2.01537) and the significance value of 0.000 <0.05. The job satisfaction variable affects the turnover intention variable by 63.3% as evidenced by the results of the coefficient of determination test that obtains an r- square value of 0.633.